(untitled) - Steel, Danielle (New York, 2023)
"From #1 New York Times bestselling author Danielle Steel comes a powerful novel about a woman running her family's luxury department store and the wealthy investor who threatens to take it over. Spencer Brooke always knew she was destined to be CEO of her grandfather's business-the most respected and luxurious department store in New York City. Brooke's has been at the center of every happy memory she has, but it hasn't been an easy journey. Seven years after her father's death, her life is very different from the days when she walked through the store with her grandfather as a young girl. She may be the owner of Brooke's, but she's also now a divorced single mother of twin boys. And with the ever-evolving landscape of the fashion industry comes new challenges for Spencer and the legacy she's inherited. Mike Weston is known for making enormous profits by transforming small businesses into bigger, more successful ones. With his marriage at a breaking point and his children grown up, investing is where he thrives-where he can build something greater. And Brooke's feels like the perfect opportunity. Yet the firm's beautiful and savvy CEO turns down the offer before they even meet. Spencer has no interest in outside investors meddling in her family business; her grandfather never saw the need for them, and neither does she. She refuses to be tempted by Mike's offer, despite her big dreams of expanding the store. But when bad luck strikes, suddenly she is backed into a corner. In Worthy Opponents, Danielle Steel crafts a thrilling story about a powerful woman-and her equally formidable opponent"--
Keywords: Romance